Sensor placement based on FE modal analysis: Dynamic characteristic of cable stayed Penang (I) bridge - Mohammed, Mohammed Idris; Mustapha, Faizal/F; Sulaeman, Erwin; Majid, Dayang Laila (Fast Track Publications, 2017)
There is a fast-growing interest to monitor the dynamic behavior of cable stayed bridges due to their long spans leading to complexity of their structures. These bridges are evolved for a long term structural health monitoring method since their performance is challenged with mixture type of traffic loading daily. This paper is aimed to propose sensors positioning at dead load condition. Finite element analysis is effective and accurate approach to certain extend used to determine the highly stressed grid points due to vibration of the bridge members. The bridge in concern is cable stayed Harp type of Penang (I) bridge. The findings based on analytical modal analysis reveals that the number of sensors to be positioned were 66 locations of the cable stayed bridge.